DETERMINATION OF SIZE OF THE EMITTING REGION IN ECLIPSING CATACLYSMIC VARIABLE STARS - Andronov, I. L.; Andrych, K. D. (Одеські астрономічні публікації, 2014)
The dependencies of the phase of eclipse of the white dwarf’s centre and the durations of the ascending and descending branches of the light curve on the binary system’s parameters were computed using the spherically symmetric approximation and the more accurate model of the elliptical projection onto the celestial sphere of the companion (red dwarf) that fills its Roche lobe. The parameters of eclipses in the classical eclipsing polar OTJ 071126+440405 = CSS 081231:071126+440405 were estimated